Problems of optimizing the production and export of environmentally friendly consumer products in Azerbaijan - Khalilov, Ilgar; Eminov, Farhad (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
State of the problem. In the article, it is justified that the provision of a green economy based on environmentalization, modernization, innovation and new technologies in the production and processing of agricultural products leads to a radical improvement of production, protection of natural capital and ecosystem services, and reduction of pollution and greenhouse gas emissions. It was noted that the regulation of agricultural production systems in the country requires the expansion of agricultural practices that increase productivity and production, contribute to the protection of ecosystems, adaptation to climate change, extreme weather events, droughts, and floods. Research object. It is the production, processing, consumption and export of agricultural products of Azerbaijan. The purpose of the study is to promote the production of ecologically clean and export-important consumer products in Azerbaijan and the stimulation of its export. Introducing the country to the world with branded products, attracting foreign investments to this field, increasing the population’s interest in the agricultural field, and attracting innovative technology to the field are also considered important. It is the determination of the damage caused by the impact on the agricultural sector and nature due to the degradation of the growing environmental components. Minimizing losses at this stage and optimizing the development of the agro-industrial complex is one of the main factors. Methodology. Generalization, historical, statistical, systematic analysis and comparison methods were used in the preparation of the article. Scientific novelty of the research. Implementation of the production and processing of ecologically clean agro-industrial products that do not harm human health and the environment, regular monitoring of the ecological condition of the soil, and the provision of increasing the production and assortment of ecologically clean export-oriented food and light industrial products. Research results. In the article, it is explained that the development of the green economy in Azerbaijan is an integral part of the state policy, and it occupies an important place in the state administration, on the example of export-oriented food and light industrial products. It is noted that the sustainability of the development of the green economy acts as a criterion for the production of competitive products of the state, which contributes positively to the provision of people’s vital needs.